STRATEGIC ANALYSIS OF E-COMMERCE IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2022)
This thesis is devoted to defining and solving problems of the development of electronic commerce in Uzbekistan. We analysed the main web-sites in Uzbekistan online market. Research findings have been identified by using PEST method